Peran Edukasi Kesehatan Dalam Meningkatkan Perilaku Hidup Bersih Dan Sehat Mahasiswa Di Sekolah Tinggi Ilmu Kesehatan Mitra Sejati - Vicky Arfeni Warongan; Rani Cahya; Revi Khairunnisa (STIKES Columbia Asia Medan, 2025)
Health counseling is one of the strategic approaches to increase students' knowledge and awareness of the importance of maintaining holistic health which includes physical, mental, social, and reproductive aspects. This activity will be held on March 19, 2025 at Sekolah Tinggi Ilmu Kesehatan Mitra Sejati with interactive lecture methods and educational games